Accuracy of Clinical Protocols in SPECT. - Kurt A; Bor D; Tastan S; Donmez S; Haciosmanoglu T (Journal of Nuclear Medicine Technology, 2012)
The accuracy of clinical SPECT is highly dependent on the acquisition and processing parameters, which are selected according to the clinical task. These parameters are usually set within protocols in order to allow for standardization from one study to another and to speed up the clinical routine. METHODS: In the first part of this work, tomographic images of a Jaszczak phantom were obtained on 5 different SPECT systems using 2 common clinical protocols and each system's default acquisition and processing parameters. In the second part, tomographic images of the Jaszczak phantom were obtained using identical acquisition and processing parameters on all systems. Projection data were then transferred to other system software for reconstruction. RESULTS: For the first part of the work, variation in image quality was seen quantitatively among the systems, even when clinical protocols with the same aim were used. The accuracy of the similar reconstruction algorithms and data transfer was determined and summarized. In the second part of this study, the performance of the SPECT systems using similar acquisition protocols and reconstruction software was determined and summarized. CONCLUSION: The default clinical protocols offered by the manufacturer for similar studies may be different from one another. The user should modify these protocols using phantom studies and standardize same-purpose protocols among different software programs.